Advancements in Process Control and Monitoring for Enhanced Efficiency and Quality - Ujban Hussain; Samiksha Sandeep Tammewar; Yashika Bhattad (Proceedings)
Introduction: Process control and monitoring are indispensable for ensuring efficiency and quality across diverse industrial applications [...]